The Attack Rate of Pocket Caterpillar (Metisa plana) And How To Control It on Oil Palm (Elaeis Guineensis Jacq) Plantation At PT Umada Pernantian â€œAâ€, North of Labuhanbatu Regency - Siallagan, Ricardo; Lestari, Widya; Adam, Dini Hariyati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Oil palm (Elaeis guineensis jacq.), is a vegetable oil-producing plant, which cannot be separated from the attack of caterpillars that eat oil palm leaves which can cause a decrease in plant production. The purpose of this study was to determine the attack rate of bagworm (Metisa plana) and how to control it, on each oil palm plant block at PT. Umada Pernantian "A", Kec. Marbau, North Labuhan Batu Regency. The method used in this research is descriptive method by collecting primary data and secondary data. Primary data is the result of observations in the field with a pest census using a descriptive method. Secondary data is data from the previous pest census in the company. The highest attack rate of Metisa plana was found in block I and block II with an incidence of 18% in block I and 8% in block II, the number of pests in block I was 27,336, and 18,480 in block II, which was >5 tails / midrib with weight category. The lowest Metisa plana attack rate was found in block III and block V where the percentage of bagworm attacks in block III: 0.08% and in block V: 0.11%, the number of pests in block III: 23 tails and block V: 26 tails, with an attack rate of <2 bagworms per midrib. After chemical control was carried out in blocks I and II, the percentage of attacks in block I: 0.43% and block II: 0.34%, the number of pests in block I: 100 and 70 in block II, the attack rate in block I and II were being <2 tails/midrib in the light category